Laboratory Scale Modelling and the Treatment of Biomedical Wastes Through Herbaceuticals for Manure Production - D. Viswanath, E.; Balasundaram, N.; Senthil Vadivel, T. (International Journal of Engineering and Technology, 2018)
Biomedical waste disposal practices are becoming important in both the developing and developed countries and need to be properly followed by the human being. An effective utilization of waste helps to have potent products like biofertilizer, bio-manure and also mineral resources like Ca, Mg, Fe, Co etc. The present study involves the treatment of biomedical waste by applying primary treatment using seaweeds (Padina tetrastromatica and Amphiroa fragilissima) and herboceuticals (turmeric & neem extracts). The experiments were designed to find out the optimum concentration of the substrate, incubation period and time in the treatment process. The secondary treatment process consisted of alkaline hydrolysis process with various concentrations to treat biomedical wastes. The bacterial load and count were analysed in all the treatment processes. The final characterization of the treated waste was analysed for the potential of bio-manure production. The result revealed that the bacterial reduction efficacy and residual mass was found to be 15000 CFU/mL and 0.94 g at the end of the 4th day, whereas the efficiencies optimized by RSM for bacterial count and residual mass were 16481.6 CFU/mL and 0.5426 g respectively. It was observed that bacterial count steadily decreased from 20000 to 5 CFU/mL of sample, when the temperature range varied from 30 to 750 C. The results of bio-manure production showed that nitrogen and phosphorous contents were enriched after the treatment procedures and the moisture content was reduced to < 2 %.Â Â